Tele-Physical Activity Promotion Program among College Students during the COVID-19 Pandemic - Reem M. Basuodan; Bodor H. Bin sheeha; Nada E. Basoudan; Nada A. Abdljabbarl; Monira I. Aldhahi (Medicina, 2023)
Background and Objectives: During the COVID-19 pandemic, lockdown and distance learning affected physical activity (PA) levels among college students. The aims were to assess the effectiveness of a tele-health PA promotion program for 6 weeks, among junior college students, on PA level and on the proportion of physically active students during the pandemic. Materials and Methods: A pre–post study design was conducted on 46 students aged 19 (±0.9) years old in Saudi Arabia. The study consisted of online introductory and educational PA classes, followed by a 6-week course during which students received daily online PA promotive messages. Wilcoxon signed-rank and McNemar’s tests were used to measure the mean differences in PA level and the changes in proportion of physically active students before and after the program, respectively. Results: The proportion of students who perform walking increased significantly from 47.4% to 68.4% (p = 0.02), while the number of students who perform moderate PA in their leisure time increased significantly from 38.9% to 69.4% (p = 0.02). No significant differences were detected between other PA levels. Conclusions: This program is effective in encouraging more college students to be physically active, but not in improving PA levels. Larger scale studies using PA objective measurement tools are needed.